The Legal Position of Land Ownership Certificates Issued Not In Accordance with Administrative Procedures - Abas, Devi Nurfadillah; Bawono, Bambang Tri (Jurnal Konstatering, 2023)
The purpose of this research is to find out: 1). To find out and analyze the legal position of land ownership certificates that were issued not in accordance with administrative procedures at the Office of the National Land Agency in Bau-Bau City. 2). To find out and analyze the responsibilities of the Head of the Land Office of Bau-Bau City for the issuance of land ownership certificates that are not in accordance with the procedure. The approach method used in discussing the problem of this research is a sociological juridical approach. The research specifications used are analytical descriptive research. Types of data using primary and secondary data obtained through interviews and literature. The data analysis method used is qualitative. The results of the study concluded: 1). The legal position of the certificate of ownership rights to land that is issued is not in accordance with administrative procedures, namely the certificate of ownership rights can be canceled, either through the administrative settlement route by the National Land Agency or through the dispute resolution pathway by the court and of course must go through the existing procedures and also the applicant must be able to prove that the object is indeed his property. The position of the certificate plays a very important role in land disputes, because the certificate is a strong documentary evidence in various matters, especially for land disputes. The legal force of land title certificates is a guarantee of legal certainty for the certificate holder. Because this is a strong proof of ownership, meaning as long as it is not proven otherwise by other parties who feel entitled and have evidence to prove it, in this case the certificate has material legal certainty (negative publication with positive elements) which is adhered to in national land law. , but on the other hand the certificate also has formal legal certainty (positive publication), namely the legal certainty of a certificate containing written provisions contained in laws or other regulations is absolute, meaning it cannot be contested. 2). The response from the head of the Bau-Bau City Land Office is in accordance with PMNA/Head of BPN provisions No. 21 of 2020 concerning the handling and settlement of land cases by a decision of the Head of the National Land Agency or by delegating it to the Regional Office or a designated official. According to Article 29 paragraph (1) letter b states that "BPN RI is obliged to implement a court decision that has obtained permanent legal force, unless there is a valid reason not to carry it out". So BPN is obliged to implement the court's decision regarding the cancellation of the certificate or revoke the certificate. Keywords: Administration; Certificate; Procedure .